2017
DOI: 10.1093/mnras/stx1562
|View full text |Cite
|
Sign up to set email alerts
|

Detection of X-ray spectral state transitions in mini-outbursts of black hole transient GRS 1739−278

Abstract: We report the detection of the state transitions and hysteresis effect in the two minioutbursts of the black hole (BH) transient GRS 1739−278 following its 2014 major outburst. The X-ray spectral evolutions in these two mini-outbursts are similar to the major outburst, in spite of their peak luminosities and the outburst durations are one order of magnitude lower. We found the L hard−to−soft and the L peak,soft of the mini-outbursts also follow the correlation previous found in other X-ray binaries. The L hard… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 69 publications
1
45
0
Order By: Relevance
“…As shown in the top panel of Figure 1, state transitions, typically observed in the main outbursts, are also observed in the first two mini-outbursts. Note that Yan & Yu (2017b) found that the much-fainter soft state in mini-outbursts likely follows the same tight L bol ∝ T 4 (bolometric luminosity L bol and representative temperature of the cold disk T ) relationship as determined by that in the major 2014 outburst, suggesting that the cold disk is also not truncated in these soft states of mini-outbursts.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…As shown in the top panel of Figure 1, state transitions, typically observed in the main outbursts, are also observed in the first two mini-outbursts. Note that Yan & Yu (2017b) found that the much-fainter soft state in mini-outbursts likely follows the same tight L bol ∝ T 4 (bolometric luminosity L bol and representative temperature of the cold disk T ) relationship as determined by that in the major 2014 outburst, suggesting that the cold disk is also not truncated in these soft states of mini-outbursts.…”
Section: Resultsmentioning
confidence: 53%
“…21 (MJD 57194), that the system is in the soft state. 4 The X-ray observations show that this source enters into the soft state about 3 days ago, on MJD 57191 (more accurately, between MJD 57190.48 and MJD 57191.67, see Figure 1 and Yan & Yu 2017b.). As shown in Figure 3, the X-ray spectrum on MJD 57194 is wellfitted under the adopted model, where the disk component contributes ≈ 88% of total flux in 1-10 keV.…”
Section: Radio Evolution In Intermediate and Soft Statesmentioning
confidence: 74%
See 3 more Smart Citations